Text Editions of (Abnormal) Hieratic, Demotic, Greek, Latin and Coptic Papyri and Ostraca : Some people love their friends even when they are far away: Festschrift in Honour of Francisca A.J. Hoogendijk - Loon, Guus A.J.C. van,; Stolk, Joanne Vera, (Papyrologica Lugduno-Batava ;, 2021)
This volume is a Festschrift in honour of Francisca Hoogendijk, containing contributions by forty friends, colleagues and former students. It includes fifty-six editions and re-editions of (Abnormal) Hieratic, Demotic, Greek, Latin and Coptic texts, most of them from Ancient Egypt. The texts are as diverse as the jubilee's own range of interests and her extensive papyrological network, including both literary and documentary texts, written on papyri and potsherds, dating from the twelfth century BCE to the eighth century CE. All texts are published with transcriptions, translations, commentary and photographs.